LAW ENFORCEMENT ON DRUG ABUSE PERPETRATORS COMMITTED BY INDONESIAN POLICEMEN - Winarno, Hadi; Amiq, Bahrul; Prawesthi, Wahyu (jfpublisher, 2023)
The regulation concerning drug is regulated on Law No. 35/2009, it is used to ensure its adequacy for the interests of science and health and prevent the drug abusement, and eradicate the illegal distribution of drugs. The cases that engaged Indonesian policemen on drug abusement criminal must have special attention in order to disappear this criminal act. These crimes cannot be considered normal, and law enforcement must be strictly enforced. This research aims to examine and analyze law enforcements on drug abuse perpetrators committed by Indonesian Policemen through law, regulations and court justice. The type of research used juridical-normative to analyze secondary data in the form of legal materials, especially primary legal and secondary legal materials. Based on the research result, when a police commits in a drug abuse offense and has the evidence, he/she may obtain criminal sanctions, such as imprisonment and fines that are determined by the type of drug abuse he/she committed. After obtaining a criminal sanction determined by the general court and has permanent force, the police officer is subject to sanctions for violating the police professional ethics code called dishonorable dismissal (PTDH).